Ameliorating Effect of Pistachio Hydroalcoholic Extract on Cisplatin-Induced Nephrotoxicity in Mice - Elham Hakimizadeh; Ayat Kaeidi; Jalal Hassanshahi; Mehrzad Mehrbani; Mohammadreza Rahmani; Iman Fatemi* (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Cisplatin-induced nephrotoxicity accompanies increased oxidative stress, leading eventually to kidney dysfunction. On the other hand, Pistacia vera nuts (pistachio) display multiple pharmacological effects such as antioxidant property. The present study investigated the effects of pistachio hydroalcoholic extract on nephrotoxicity induced by cisplatin in mice. Methods: Pistachios (100 g) were powdered and macerated in 1 L of ethanol (80%) for 72 h Then, dried with rotary evaporator apparatus. Forty male mice were divided into five groups: normal, cisplatin, cisplatin+DMSO, cisplatin+ pistachio hydroalcoholic extract 10, and cisplatin+ pistachio hydroalcoholic extract 100. Nephrotoxicity was induced by intraperitoneal injection of cisplatin (20 mg/kg/day) on the first day of the experiment. Pistachio hydroalcoholic extract (10 and 100 mg/kg/p.o) was administered for four consecutive days. The body weight and kidney function indices such as serum creatinine (Cr) and blood urine nitrogen (BUN) were measured. Also, the renal tissues were assessed for levels of malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx). Results: Cisplatin reduced animals' body weight. Also, cisplatin increased levels of Cr, BUN, and MDA, and decreased the activities of SOD, CAT, and GPx. Treatment with pistachio hydroalcoholic extract (100 mg/kg) reduced the levels of serum Cr, BUN, as well as renal MDA. Moreover, administration of 100 mg/kg pistachio hydroalcoholic extract to cisplatin-treated mice increased the body weight as well as CAT, GPx, and SOD activities. Conclusion: These results imply that pistachio hydroalcoholic extract treatment may diminish cisplatin-induced renal dysfunction through reduction of oxidative stress in the kidney tissue.